1994
DOI: 10.1007/978-94-017-1671-0_17
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional protein electrophoretic analysis of postponed aging in Drosophila

Abstract: Five populations of Drosophila melanogaster that had been selected for postponed aging were compared with five control populations using two-dimensional protein gel electrophoresis. The goals of the study were to identify specific proteins associated with postponed aging and to survey the population genetics of the response to selection. A total of 321 proteins were resolvable per population; these proteins were scored according to their intensity. The resulting data were analyzed using resampling, combinatori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…From such theory it follows that many loci, and many biochemical pathways, are expected to produce the deleterious effects of ageing, because it is a secondary side-effect of normal evolution. Earlier, less definitive work using selected stocks [9] indicated that many loci contribute to ageing in Drosophila [10,11]. So Pletcher et al [1] are probably correct to implicate hundreds of loci in the control of Drosophila ageing.…”
Section: Some Of the Earliest Experimental Research On Ageing Was That Of Raymond Pearl [3] On The Duration Of Life Inmentioning
confidence: 99%
“…From such theory it follows that many loci, and many biochemical pathways, are expected to produce the deleterious effects of ageing, because it is a secondary side-effect of normal evolution. Earlier, less definitive work using selected stocks [9] indicated that many loci contribute to ageing in Drosophila [10,11]. So Pletcher et al [1] are probably correct to implicate hundreds of loci in the control of Drosophila ageing.…”
Section: Some Of the Earliest Experimental Research On Ageing Was That Of Raymond Pearl [3] On The Duration Of Life Inmentioning
confidence: 99%
“…For instance, it has been estimated that >lo0 loci may be involved in aging in Drosophila based on comparisons of polypeptides found in long-lived strains (selected on the basis of late reproduction) and nonselected "short-lived" strains [Fleming et al, 1993; Rose, 19841. Nevertheless, it has been possible by analysis of hybrids formed between long-lived and short-lived strains to show the presence of both additive and nonadditive genetic determinants and to show that most of the additive effects seem t o reside on the third chromosome [Luckinbill et al, 1988;Buck et al, 19931. In C. elegans, where hybrid vigor does not complicate genetic analysis [Johnson and Wood, 19821, progress in localizing longevity determinants has been more rapid.…”
Section: Mapping Longevity Determinantsmentioning
confidence: 99%
“…Many of these pathways are already considered candidates for pharmaceutical modulation (Melov et al ., 2000(Melov et al ., , 2001Lonn et al ., 2002;Evason et al ., 2005). However, the treatment of aging is highly likely to involve secondary and nonadditive effects, given the multifold pathways that affect aging (Fleming et al ., 1993;Pletcher et al ., 2002;Rose & Long, 2002). Therefore, the most reasonable expectation is that particular pharmaceuticals that affect aging may do so through multiple pathways, not just the pathway that is of a priori interest.…”
Section: Introductionmentioning
confidence: 99%